Peripartum echocardiographic changes in women with hypertensive disorders of pregnancy. (8th February 2022) - Giorgione, V.; O'Driscoll, J.; Coutinho, C. M.; Di Fabrizio, C.; Sharma, R.; Khalil, A.; Thilaganathan, B.
ABSTRACT: Objective: Hypertensive disorders of pregnancy (HDP) are associated with significant myocardial dysfunction on echocardiography. The impact of hemodynamic changes related to volume redistribution following delivery on myocardial function in women with HDP has not been evaluated systematically. The aim of this study was to compare echocardiographic findings immediately before and after delivery in women with HDP. Methods: This was a prospective longitudinal study including 30 women with a diagnosis of HDP who underwent two consecutive transthoracic echocardiographic (TTE) examinations, before delivery and in the early postpartum period. Paired comparisons of the findings from the two assessments were performed. Results: Left‐ventricular (LV) concentric remodeling or hypertrophy was detected in 21 (70%) patients. There was no significant difference in cardiac morphology indices such as LV mass index (78.9 ± 16.3 g/m 2 vs 77.9 ± 15.4 g/m 2 ; P = 0.611) or relative wall thickness (0.45 ± 0.1 vs 0.44 ± 0.1; P = 0.453) before vs after delivery. LV diastolic function did not demonstrate any peripartum variation, with similar left‐atrial volume (52.4 ± 15.3 mL vs 51.0 ± 15.6 mL; P = 0.433), lateral E′ (0.12 ± 0.03 m/s vs 0.12 ± 0.03 m/s; P = 0.307) and E/E′ ratio (7.9 ± 2.2 vs 7.9 ± 1.7; P = 0.934) before vs after delivery. Systolic function indices, such as LV ejection fraction (57.5 ± 3.4% vs 56.4 ± 2.1%; P = 0.295) and global longitudinal strain (−15.3 ± 2.6% vs −15.1 ± 3.1%; P = 0.582), also remained unchanged between before vs after delivery. Conclusions: Maternal hemodynamic changes associated with delivery did not influence significantly peripartum TTE indices in women with HDP. Suboptimal maternal echocardiographic findings in HDP are likely to be the consequence of chronic pregnancy cardiovascular load changes or pre‐existing maternal cardiovascular impairment. Severity and persistence of myocardial dysfunction in the postpartum period may be related to the long‐term maternal cardiovascular disease legacy of HDP. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.